From hell being a melodrama in sixteen parts - Moore, Alan 1953-; Mullins, Pete.; Campbell, Eddie 1955-. (Marietta, Ga. Top Shelf Productions, 2006)
Dramatizes the Jack the Ripper murders in graphic novel form, and includes author commentary and an appendix, "Dance of the Gull Catchers." Contains adult content
Keywords: Jack -- the Ripper -- Comic books, strips, etc. -- Fiction; Horror comic books, strips, etc